Workload: a comparison between the online and observational methods - Rute Merlo Somensi; Rita Catalina Aquino Caregnato; Gustavo Henrique Cervi; Cecilia Dias Flores
ABSTRACT Objective: To measure nursing Workload (WL) of nurses who work in the Inpatient Unit, as recommended by the Nursing Interventions Classification (NIC), comparing observational and online methods to propose supervision strategies for academic professionals. Method: Quantitative, descriptive, observational study performed in a Clinical/Surgical Hospital Unit. 30 direct and indirect activities. Data collected in observational and online records. Statistical analysis: SPSS 18.0 software, percentage frequencies and associated times between groups by Fisher's Exact test, 95% confidence interval, significance level 5%. Results: Comparing the activities performed with the NIC time: from the direct 16, five observational and five online, were out of range, with no significant difference between frequencies (P=0.427). Of the 14 indirect, only in the observational, two were out of the range, without significant difference (P=0.486). Conclusion: Both methods measure WL; the online method developed accompanies activities performed in real time.